A Neuro-fuzzy Approach to Part Fitup Fault Control During Resistance Spot Welding Using Servo Gun - Zhang, Y. S.; Chen, G. L (Advances in Natural Computation, 2005)
Resistance spot welding (RSW) is widely utilized as a joining technique for automobile industry. However, good weld quality control method has not yet been developed in plant environment when part fitup fault exists. This paper proposed a neuro-fuzzy algorithm to control weld quality by adjusting welding current. An experimental system was developed to measure electrode displacement curve. Accordingly based on electrode displacement curve optimal current for every cycle will be achieved under poor fitup fault condition. Results showed that proposed neuro-fuzzy system is suitable as a weld quality monitoring for resistance spot welding.